Evaluación del desarrollo de la vicia (Vicia sativa L.) y avena (Avena sativa L.) en el suelo erosionado, con base de tres abonos orgánicos a diferentes dosis en el sector Salache, Cantón Latacunga, Provincia de Cotopaxi 2021 - Morocho Morocho, Jonathan Bladimir (2021)
The purpose of this research was the study of eroded soil in the Technical University of Cotopaxi, Salache sector, at an altitude of 2800 meters above sea level, in a sandy loam soil, the development of vetch (Vicia sativa L.) and oats (Avena sativa L.) was evaluated in the eroded soil based on three organic fertilizers at different doses in the Salache sector, Canton Latacunga, province of Cotopaxi 2021. In this work, a completely randomized block design was applied with a factorial arrangement of 3*3+1, with 3 replications and 30 experimental units. The research results indicate that the best result in the variable germination percentage of both vicia and oats is the guinea pig manure was excellent with 48.22% to 50.44%, in the research. As for the variable % in germination in treatments in both vicia and oats, the treatments had a homogeneity from 15 days to 60 days, as for the variable of vetch and oats the best result of the stem diameter of vetch is the T2 (Eco fertilizer with 30 t/ha) at 60 days with 2.8cm, in oats is the T8 (guinea pig manure 30 t/ha), at 45 days 3.33cm and 60 days 4.9cm, and T7 (guinea pig manure 20 t/ha) at 60 days 4.9cm, were the best results of this research, for the result the best in terms of pest incidence is Treatment T1 (eco fertilizer 20 t/ha) with 0.77%, for which the best results obtained the best treatment is T2 (eco fertilizer 30 t/ha) for an adequate development associated with viti-avena in the eroded soil of Salache, and with alternative incorporation as green manure for the recovery of poor soil fertility.